1990
DOI: 10.1055/s-2007-1024847
|View full text |Cite
|
Sign up to set email alerts
|

III. Effects of Chronic Hypoxia on Muscle Enzyme Activities*

Abstract: Biopsies from the vastus lateralis muscle of seven participants in the Swiss expedition to Mt. Everest and Lhotse in 1986 were taken before departure to and after return from high altitude, and used for measurements of maximal activities of 12 reference enzymes of anaerobic and aerobic-oxidative metabolic pathways. The results indicated that strenuous exercise at high altitude induced increases in enzyme activities of glycolysis and decreases in enzyme activities of terminal substrate oxidation (the citric aci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
115
1
9

Year Published

1996
1996
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 161 publications
(131 citation statements)
references
References 7 publications
6
115
1
9
Order By: Relevance
“…CK and COX enzyme activities. The activities of CK and COX from pre-and poststimulated muscles were spectrophotometrically determined by standard methods (21) and expressed in U (µmol substrate consumed/min)/g wet wt muscle. Statistical analysis.…”
Section: Nmes Protocolmentioning
confidence: 99%
“…CK and COX enzyme activities. The activities of CK and COX from pre-and poststimulated muscles were spectrophotometrically determined by standard methods (21) and expressed in U (µmol substrate consumed/min)/g wet wt muscle. Statistical analysis.…”
Section: Nmes Protocolmentioning
confidence: 99%
“…Laboratory rats and humans are most commonly used in this type of experiment. Short-term exposure to low oxygen levels through either exercise (in rats: Constable et al, 1987;in humans: Holloszy, 1967;Baldwin et al, 1973;Terrados et al, 1990), normobaric hypoxia (in rats: Daneshrad et al, 2000;in humans: Desplanches et al, 1993) or hypobaric hypoxia (in humans: MacDougall et al, 1991;Hoppeler and Desplanches, 1992;Howald et al, 1990) has produced mixed results. Previous studies have demonstrated that activities of oxidative marker enzymes can be elevated (in humans: Holloszy, 1967;Desplanches et al, 1993;Terrados et al, 1990), decreased (in humans: Hoppeler and Desplanches, 1992;Howald et al, 1990) or show no change (in rats: Daneshrad et al, 2000;in humans: Holloszy, 1975) during the process of hypoxic acclimation.…”
mentioning
confidence: 99%
“…Short-term exposure to low oxygen levels through either exercise (in rats: Constable et al, 1987;in humans: Holloszy, 1967;Baldwin et al, 1973;Terrados et al, 1990), normobaric hypoxia (in rats: Daneshrad et al, 2000;in humans: Desplanches et al, 1993) or hypobaric hypoxia (in humans: MacDougall et al, 1991;Hoppeler and Desplanches, 1992;Howald et al, 1990) has produced mixed results. Previous studies have demonstrated that activities of oxidative marker enzymes can be elevated (in humans: Holloszy, 1967;Desplanches et al, 1993;Terrados et al, 1990), decreased (in humans: Hoppeler and Desplanches, 1992;Howald et al, 1990) or show no change (in rats: Daneshrad et al, 2000;in humans: Holloszy, 1975) during the process of hypoxic acclimation. Activities of enzymes that catalyze glycolytic and anaerobic reactions have been shown to either decrease (in rats: Constable et al, 1987;in humans: Baldwin et al, 1973;Holloszy, 1975;Terrados et al, 1990) or remain constant (in humans: Holloszy and Oscai, 1969;Howald et al, 1990) when animals are acclimated to hypoxia.…”
mentioning
confidence: 99%
“…Bu değişiklikler yüksek rakımlı yerlerde yaşayan sağlıklı insanlarda veya kronik kalp yetersizliği, periferik arter hastalığı, kronik tıkayıcı akciğer hastalığı gibi hastalıkları olup kronik hipoksiye maruz kalanlarda karakteristik olarak görünür. [11][12][13][14][15][16][17] Bu ikinci gruptaki hastalarda kaslarda atrofi (kas lifi çapında azalma), tip 2 kas yapısına doğu kayma ve fosfofruktokinaz enzim aktivitesinde, hız sınırlayıcı glikolitik enzimde, mitokondriyal elektron transport sisteminin terminal enzimi olan sitoktom oksizda da artış görünür. [17,18] Sauleda ve ark.…”
Section: Discussionunclassified